Russia and the World in the Putin Era from theory to reality in Russian global strategy - Kanet, Roger E. 1936-; Moulioukova, Dina (Routledge Global Security Studies, 2021)
Intro -- Half Title -- Series Page -- Title Page -- Copyright Page -- Contents -- Contributors -- Preface -- Note -- Introduction: Russia foreign policy and the return to authoritarian roots -- Notes -- Bibliography -- Part I: Sources and tools of Russian foreign policy -- 1. Russia's self-image as a great power -- Russia as a great power -- Russia as an empire -- The role of the West -- The break in biographical continuity -- Notes -- References -- 2. Russian strategic culture and renewed conflict with the West -- The turn toward the West followed by Putin's "great power" narrative -- Strategic culture and Russian foreign policy -- From the Yeltsin honeymoon to Putin's policy shift -- Russia vs. NATO and the EU: the gas wars and the war in Georgia -- From the failed Obama-Medvedev "reset" to the Ukraine crisis -- The Eurasian Union and the Ukraine crisis -- A new cold war and the Russian challenge to the liberal world order -- Donald Trump's impact on East-West relations -- Notes -- References -- 3. Images and decision-making in foreign policy: the case of Vladimir Putin -- Introduction -- Images in international relations theory: the received wisdom -- Mapping images: the theory revisited -- Vladimir Putin: his foundational image and his image of the Syrian civil war -- President Putin's first core belief: the ontological centrality of states -- President Putin's second core belief: preserving the dagger and not feeding the enemy's army -- President Putin's third core belief: keeping Chekhov's rifle from going off -- President Putin's fourth core belief: great powers' as custodians of international society -- President Putin's image of the Syrian civil war -- Conclusion and the path forward -- Notes -- References -- 4. Atlanticism in an age of great power competition: is Russia achieving its goals? -- Introduction -- The Ukraine crisis.